2020
DOI: 10.1177/1533033820945806
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lymph Node Density in Patients With T3 and T4 Pyriform Sinus Carcinoma

Abstract: Background/Aim: Lymph node density is a parameter used to more accurately predict tumor recurrence and patient survival. However, its association with surgical outcome in pyriform sinus carcinoma remains unclear. The purpose of this study was to assess the prognostic value of lymph node density in advanced pyriform sinus carcinoma. Patients and Methods: A total of 87 patients with pyriform sinus carcinoma treated between 2008 and 2015 were enrolled. Then, 5-year overall survival, 5-year disease-specific surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…Cox multivariate analysis revealed that N stage is an independent risk factor. This result was consistent with the findings of related studies (15,16). All these results indicated that N staging is of great importance to the prognosis of patients and suggested that the cervical The affected side of level VI lymph nodes is thoroughly dissected strictly along the thyroid surgical capsule after dealing with the superior polar thyroid vessels of the thyroid gland of the affected side is not invaded.…”
Section: Discussionsupporting
confidence: 94%
“…Cox multivariate analysis revealed that N stage is an independent risk factor. This result was consistent with the findings of related studies (15,16). All these results indicated that N staging is of great importance to the prognosis of patients and suggested that the cervical The affected side of level VI lymph nodes is thoroughly dissected strictly along the thyroid surgical capsule after dealing with the superior polar thyroid vessels of the thyroid gland of the affected side is not invaded.…”
Section: Discussionsupporting
confidence: 94%